(untitled) (European Journal of Marketing and Economics, 2026)
In the article, a phenomenon of urbanization of Latin America was analysed in terms of its impact on the level of competitiveness of the cities. A role that cities play in Latin America’s economy was emphasized. The author has examined a number of reliable reports on competitiveness of the cities and on this basis formulated its assessment of the level of competitiveness on a global basis, including identifying strengths and weaknesses of the cities, key areas for strong economic development and proposes recommendations. Based on the analysis of available data and source reports, the main trends in urbanization have been identified that may affect the dynamics of the Latin American city’s competitiveness. Latin America is the most urbanized developing region in the world. Since 1950, Latin America urbanized at an exceptional rate, raising its urban population as per cent of total from 50 per cent to 82 per cent now. This figure is expected to grow to 86 per cent by 2050. Brazil and the southern cone may reach that level by 2020. In 2015, as much as 13% of world’s urban population lived in Latin America. São Paulo, Mexico City, Lima or Bogota are examples of the largest cities in the world, with an ever increasing number of inhabitants. Over the past two decades, the region’s urban population and economic growth has been increasingly taking place also in intermediate-sized cities, which are expanding exponentially.